Eastern Association for the Surgery of Trauma Multicenter Trial: Comparison of pre-injury antithrombotic use and reversal strategies among severe traumatic brain injury patients. Issue 1 (January 2022) - Yorkgitis, Brian K.; Tatum, Danielle M.; Taghavi, Sharven; Schroeppel, Thomas J.; Noorbakhsh, Matthew R.; Philps, Frances Hite; Bugaev, Nikolay; Mukherjee, Kaushik; Bellora, Mellody; Ong, Adrian W.; Ratnasekera, Asanthi; Nordham, Kristen D.; et al.
Abstract : BACKGROUND: Trauma teams are often faced with patients on antithrombotic (AT) drugs, which is challenging when bleeding occurs. We sought to compare the effects of different AT medications on head injury severity and hypothesized that AT reversal would not improve mortality in severe traumatic brain injury (TBI) patients. METHODS: An Eastern Association for the Surgery of Trauma–sponsored prospective, multicentered, observational study of 15 trauma centers was performed. Patient demographics, injury burden, comorbidities, AT agents, and reversal attempts were collected. Outcomes of interest were head injury severity and in-hospital mortality. RESULTS: Analysis was performed on 2, 793 patients. The majority of patients were on aspirin (acetylsalicylic acid [ASA], 46.1%). Patients on a platelet chemoreceptor blocker (P2 Y12 ) had the highest mean Injury Severity Score (9.1 ± 8.1). Patients taking P2 Y12 inhibitors ± ASA, and ASA-warfarin had the highest head Abbreviated Injury Scale (AIS) mean (1.2 ± 1.6). On risk-adjusted analysis, warfarin-ASA was associated with a higher head AIS (odds ratio [OR], 2.43; 95% confidence interval [CI], 1.34–4.42) after controlling for Injury Severity Score, Charlson Comorbidity Index, initial Glasgow Coma Scale score, and initial systolic blood pressure. Among patients with severe TBI (head AIS score, ≥3) on antiplatelet therapy, reversal with desmopressin (DDAVP) and/or platelet transfusion did not improve survival (82.9% reversal vs. 90.4% none, p = 0.30). In severe TBI patients taking Xa inhibitors who received prothrombin complex concentrate, survival was not improved (84.6% reversal vs. 84.6% none, p = 0.68). With risk adjustment as described previously, mortality was not improved with reversal attempts (antiplatelet agents: OR 0.83; 85% CI, 0.12–5.9 [ p = 0.85]; Xa inhibitors: OR, 0.76; 95% CI, 0.12–4.64; p = 0.77). CONCLUSION: Reversal attempts appear to confer no mortality benefit in severe TBI patients on antiplatelet agents or Xa inhibitors. Combination therapy was associated with severity of head injury among patients taking preinjury AT therapy, with ASA-warfarin possessing the greatest risk. LEVEL OF EVIDENCE: Prognostic, level II. Abstract : Supplemental digital content is available in the text.